LEARNING ENGLISH IN BRAZIL: CHALLENGES IN THE MIDST OF THE TRANSFORMATION OF PUBLIC EDUCATION - Trebien, Heitor Augusto Colli; Curcio, Carolina Hanna; Marian, Jane; Gilz, Claudino (Caderno PAIC, 2023)
This paper aims to investigate how Brazilian scientific papers describe and question the historical landmarks of public education in Brazil, considering English language teaching. It also aims to infer what perspectives are expressed in the texts, from the beginning of the 21st Century to nowadays. The research is subsided by the findings of Brazilian education being marked by profound social disparities since the Colonial Era. Such characteristics persist to the present historical period, and its consequences result in several structural problems (such as social, educational and workforce exclusion), especially towards marginalized people. Given the scope of the investigation, a systematic review of literature was done, based on the materials extracted from Periódico Capes and Google Scholar. In order to analyze the documents, Corpus Linguistics and Content Analysis were the chosen methodologies. The 81 compiled texts consisted of papers, undergraduate thesis, master’s and doctorate’s thesis. It was noticeable in the analysis that the selected corpus focused on identifying effective ways to transform public education in Brazil, with proposals to overcome the existing challenges in each context.